Effects of Artificial Sweeteners Aspartame and Sucralose on the Size of Hepatocytes in Rat Liver - Nadia Haq, Sadia Saqib, Raafea Tafweez, Irfan Ali, Ahmad Fawad Syami (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The excessive use of artificial sweeteners now a days just to lose weight and to remain fit and due to other reasons without knowing its effects on liver gave me a thought to conduct this study to see whether they are safe or not for liver health. Objectives: The objectives of the study were to see the effects of artificial sweeteners Aspartame and Sucralose on the size of rat hepatocytes and to compare their effects to choose relatively safe artificial sweetener for routine use. Methods: Fifty adult Wistar albino rats used in this study were randomly divided into five groups. Group I (control group) animals were given drinking water by oral gavage. The animals of group II and III were given low (40mg/kg body weight) and high doses (1000mg/kg body weight) of Aspartame respectively. Similarly, animals of group IV and V were given low (5mg/kg body weight) and high doses (1000mg/kg body weight) of Sucralose respectively. Doses were given by oral gavage once daily, six days a week for a total duration of eight weeks. At the end of the experiment histological observation of liver in all animal groups was made. Results: Microscopic examination revealed that hepatocytes of group III animals (high dose group of Aspartame) had largest size with the mean value of 20.86±2.00µm as compared to the control group hepatocytes having mean value of 16.46±1.74µm. Conclusion: The increase in the size of hepatocytes was seen in high dose groups of Aspartame and Sucralose whereas changes seen in low dose groups of Aspartame and Sucralose were not significant. Keywords: Artificial sweeteners, Histology of rat liver, Size of hepatocytes.